Social Media Use among Adolescents in North Dakota, USA - Olola, Toyosi Motilola (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The study investigated the use of social media among adolescents in North Dakota. Specifically, the study sought to determine the prominent social media used by adolescents in North Dakota; and the extent to which adolescents used social media in North Dakota State. The study adopted a descriptive survey research design. The sample for the study consisted of two hundred (200) adolescents that were randomly selected using a simple random sampling technique. One research instrument tagged ‘’Adolescents Social Media Questionnaire’’ (ASMQ) was used to collect data for the study.  Data collected were analyzed using frequency counts and simple percentages. Results of the study showed that Snapchat, TikTok, Facebook, Instagram, YouTube, and Twitter are the prominent social media used by adolescents at above 70.0% in North Dakota State. Results of the study also revealed that the level of adolescents who use social media is high at 60.5% in North Dakota. The study concluded that Snapchat, TikTok, Facebook, Instagram, YouTube, and Twitter are the prominent social media used by adolescents and that the level to which adolescents use social media is high in North Dakota.